Inovasi Pemanfaatan Maggot sebagai Alternatif Pupuk Hayati dan pakan Hewan untuk KWT Sejahtera Aceh - Mulyadi, Mulyadi; Hayati, Rahmah; Rahly , Fawwa; Hafidh , M; Maulana, Firza (Pencerah, 2025)
Household organic waste management remains a significant environmental and economic challenge for small-scale farming communities. This Community Service Program (PKM) aimed to empower the Sejahtera Aceh Women Farmers Group (Kelompok Wanita Tani/KWT) through innovative utilization of maggots from Black Soldier Fly (BSF) and Tenebrio molitor (TM) as environmentally friendly and economically valuable alternatives for biofertilizer and animal feed. The program employed participatory methods, including socialization, technical training, hands-on practice, and continuous assistance in maggot cultivation and downstream product processing, namely Haggot Fertilizer and Waggot Feed. The activity involved 25 members of KWT Sejahtera Aceh in Seumereung Village, Aceh Besar Regency. The results demonstrated a substantial increase in participants’ knowledge and skills in converting household organic waste into value-added agricultural products. Haggot Fertilizer exhibited high nutrient potential, with 41% organic carbon and 9.8% potassium content, contributing to improved soil structure, water efficiency, and enhanced growth of horticultural crops. Meanwhile, Waggot Feed contained up to 40% protein, comparable to commercial pellet feed, indicating its feasibility as an alternative protein source for poultry and fish. In conclusion, this program successfully strengthened the capacity and independence of women farmers in sustainable waste management, reduced reliance on chemical inputs, and created new community-based economic opportunities. The initiative shows strong potential for replication and further development through advanced training, economic partnerships, and integration with sustainable organic farming programs.